1987
DOI: 10.2307/3430422
|View full text |Cite
|
Sign up to set email alerts
|

Initiation, Promotion, and Inhibition of Carcinogenesis in Rainbow Trout

Abstract: The identification of etiological agents in feral fish neoplasia epizootics has been hampered in part by the lack of suitable fish models, and complicated by the likely existence of environmental agents which can act to stimulate or reduce population responses to genotoxin insult. The response of fish to tumor inhibitors and promoters, and the underlying mechanisms of modulation, have been studied in the rainbow trout model. Dietary treatment of trout with the compounds indole-3-carbinol (13C), ,8-naphthofiavo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 23 publications
1
15
0
Order By: Relevance
“…Use of the trout tumor model to study modulation of carcinogenesis has been reviewed elsewhere (158)(159)(160). The historically low spontaneous liver tumor incidence (0.1%) is a significant advantage in the statistical design of multidose tumor inhibition and promotion experiments.…”
Section: Tumor Promotion and Inhibition In Troutmentioning
confidence: 99%
“…Use of the trout tumor model to study modulation of carcinogenesis has been reviewed elsewhere (158)(159)(160). The historically low spontaneous liver tumor incidence (0.1%) is a significant advantage in the statistical design of multidose tumor inhibition and promotion experiments.…”
Section: Tumor Promotion and Inhibition In Troutmentioning
confidence: 99%
“…Essentially, there is evidence that, not surrisingly, proto-oncogenes exist in fish, and presumably they can be activated by similar changes to those found in mamals. In contrast, the study of promoters in fish (Bailey et al 1987a(Bailey et al , 1987b(Bailey et al , 1988) is limited to a demonstration of the promotional effects of the PCB formulation…”
Section: Hepatocarcinogenesis In Fishmentioning
confidence: 99%
“…I3C possesses anti-carcinogenic e ects in experimental animals depending on the time of I3C exposure (Bailey et al, 1987;Dashwood, 1998;Dashwood et al, 1989;Grubbs et al, 1995). Exposure of I3C prior to carcinogenic insult had clearly shown to have protective e ect (Guo et al, 1995;Xu et al, 1996), and that I3C has been shown to inhibit the growth of human cancer cells (Katdare et al, 1998;Tiwari et al, 1994).…”
Section: Introductionmentioning
confidence: 99%